2008
DOI: 10.3201/eid1408.080444
|View full text |Cite
|
Sign up to set email alerts
|

GenotypingRickettsia prowazekiiIsolates

Abstract: We developed a typing method that can differentiate 8 strains of Rickettsia prowazekii into 7 genotypes. This method can be used to type and trace the origin of R. prowazekii isolated from samples collected during epidemics after a bioterrorism attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…1, lanes 6 and 10). In order to explore any change in the RFLP pattern depending on different strains, we compared the RFLP patterns of three R. prowazekii strains (Madrid E, Breinl, and GvV-250) with different genotyping previously reported [10], and found that the RFLP was identical for the three strains, confirming the utility of our analysis to identify the species (fig. 2).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…1, lanes 6 and 10). In order to explore any change in the RFLP pattern depending on different strains, we compared the RFLP patterns of three R. prowazekii strains (Madrid E, Breinl, and GvV-250) with different genotyping previously reported [10], and found that the RFLP was identical for the three strains, confirming the utility of our analysis to identify the species (fig. 2).…”
Section: Resultssupporting
confidence: 81%
“…Functionally, the ompB gene has been well conserved in rickettsial evolution, and has been used as a taxonomic, phylogenetic, and diagnostic tool [10, 1314]. The identity of the ompB sequence among species belonging to the same group is high, and on average the SFG Rickettsia have 96%, the TG 92%, and the TRG 91% identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the 16S–23S rDNA spacer is not usable in Rickettsia species as these genes are not contiguous (Andersson et al , 1995, 1999; Ogata et al , 2001). Genotyping studies based on the presence or absence of single‐nucleotide polymorphisms (SNP) (Karpathy, Dasch & Eremeeva, 2007; Zhu et al , 2008) and variable nucleotide tandem repeats (VNTR) (Eremeeva et al , 2006) in intergenic spacers have been applied to Rickettsia spp. Moreover, multi‐spacer typing (MST) has been developed selecting the most variable noncoding regions between R. prowazekii and R. conorii .…”
Section: Phylogeny and Taxonomymentioning
confidence: 99%
“…Due to different sources and different passages, R. prowazekii strain can be grouped in to three virulence groups: high virulence group represented by Breinl strain, medium virulence group represented by flying squirrel isolates and low virulence or non-virulence group represented by Madrid E strain and its revertant strains. All strains of R. prowazekii can be differentiated by sequencing several loci of the genome of R. prowazekii (Zhu et al, 2008). R. rickettsii strains were not genetically typed except for virulent R strain and nonvirulent Iowa strains, whose whole genomes were completely sequenced (Ellison et al, 2008).…”
Section: Experimental Vaccines and Other Potential Vaccine Prospectsmentioning
confidence: 99%